Effects of vandetanib on adenoma formation in a dextran sodium sulphate enhanced Apc(MIN/+) mouse model. - Alferez, D; Ryan, A; Goodlad, R; Wright, N; Wilkinson, R (2010)
The Apc(MIN/+) mouse is a well-characterised model of intestinal tumourigenesis in which animals develop macroscopically detectable adenomas. However, most of the adenomas are formed in the small intestine and resolution of events in the colon, the most relevant site for human disease, is limited. Inducing colitis with dextran sodium sulphate (DSS) can selectively enhance the development of lesions in the colon. We demonstrated that a DSS pre-treatment is well tolerated and effective at inducing colon adenomas in an Apc(MIN/+) mouse model. We then investigated the effect of inhibiting vascular endothelial growth factor (VEGFR)- and epidermal growth factor receptor (EGFR)-dependent signalling pathways on the development of adenomas induced in DSS-pretreated (DSS/Apc(MIN/+)) or non-DSS-pretreated (Apc(MIN/+)) mice using vandetanib (ZD6474), a potent and selective inhibitor of VEGFR and EGFR tyrosine kinase activity. Eight-week old Apc(MIN/+) mice were given either drinking water or 1.8% DSS and then vandetanib (ZD6474) (50 mg/kg/day) or vehicle by oral gavage for 28 days and sacrificed 24 h after the last dose and assessed for adenoma formation in the intestines. DSS pre-treatment was well tolerated and significantly enhanced formation of adenomas in the colon of control Apc(MIN/+) mice. Vandetanib treatment significantly reduced adenoma formation in the small intestine by 68% (P=0.001) and the colon by 77% (from 13.8 to 3.1, P=0.01) of DSS-pretreated Apc(MIN/+) mice. In the Apc(MIN/+) group, vandetanib also reduced the mean number of adenomas in the small intestine by 76% (P<0.001) and in the colon by 60% (from 3.9 to 1.5, P=0.1). DSS-pre-treatment increased the resolution of the model, allowing us to confirm statistically significant effects of vandetanib on the development and growth of colon adenomas in the Apc(MIN/+) mouse. Moreover these preclinical data provide a rationale for studying the effects of vandetanib in early stages of intestinal cancer in the clinic.